Comparison of healthcare resource utilization and medical costs between patients with seropositive and seronegative rheumatoid arthritis. (June 2021) - Kim, Hyoungyoung; Cho, Soo-Kyung; Choi, Seongmi; Im, Seul Gi; Jung, Sun-Young; Jang, Eun Jin; Sung, Yoon-Kyoung
Objectives: To compare healthcare utilization and medical costs between patients with seronegative (SN) and seropositive (SP) rheumatoid arthritis (RA). Methods: We conducted a nationwide population study using the Korean health insurance claims database in 2016. We divided patients with RA into SN and SP groups and compared healthcare utilization including medications, medical utilization, and direct medical costs for 1 year between the groups in a cross-sectional analysis. Differences in costs between patients with SPRA and SNRA were assessed using the quantile regression model. We performed longitudinal analysis using data from 2012 and 2016 to examine changes over time. Results: A total of 103, 815 SPRA and 75, 809 SNRA patients were included in the analyses. The SPRA group used significantly more methotrexate (73.2% versus 30.3%) and biologic agents (7.9% versus 2.9%) than the SNRA group. The number of RA-related outpatient visits [6.0 ± 3.7 versus 4.4 ± 4.0 times/year, standardized difference (SD) = 0.41] and annual medical costs per patient (1027 versus 450/year, SD = 0.25) were higher in the SPRA group than the SNRA group. Quantile regression results indicated that the incremental cost of seropositivity on total medical costs of RA patients gradually increased as medical costs approached the upper quantile. The annual direct medical costs for each patient between 2012 and 2016 increased in both groups: by 25.1% in the SPRA group and 37.6% in the SNRA group. Conclusion: Annual RA-related direct medical costs and RA-related healthcare utilization per patient are higher in patients with SPRA than those with SNRA.